Pedagogia Hospitalar: Trabalho Pedagógico, Ensino e Aprendizagem e Fatores de Aproximação - Oliveira, Geicinara Martins de Almeida (2023)
This research presents a study about the organization of the pedagogical work in hospitals affiliated with the Service of treatment to the Hospital schooling chain (Sareh), in Cascavel/PR. The hospital is commonly comprehended as a place of sad aspect and unwanted for the most part of people, therefore, go through hospitalization is a situation that can bring some damages to the student. In front of this, the aim of this work is to understand how the pedagogical work is developed is the hospital environment through the Sareh and reflect about the implications of this program in the process of teaching learning of the hospitalized students. In that regard, the inicial qualification of a pedagogue is investigated and the difficulties faced in the function, it reflects about the adjustments performed in hospitals with view to a humanized pedagogical treatment and, still, the perception of the multiprofessional group is analised about the hospital pedagogical work. The way of this research happened from the bibliographic research around the posts of unknown authors about the issue; furthermore, we appealed to the descriptive research in field, whereby the obtained datas are analised in a determined population. The theoretical source on which the researcher used were the articles, books, dissertations and thesis, leaning on authors such as Matos e Muggiati (2009), Mutti (2016) and Menezes (2018). The treatment of the obtained datas followed the theoretical and methodological presupposed of the Content Analysis of Bardin (1977). The study is justified by the educational and social relevancy of the issue, highlighting the nuances and the challenges faced by the educators in the process of teaching-learning of the hospitalized student, in order to promote the self-reflection in the educators, besides discutions between autorities responsible for the criation of educational politics. The affiliated hospitals with Sareh in Cascavel-PR, are entrusted of answer the students from State Education Chain, nevertheless, the high demand is still big. In this way, this study suggests debates about the pedagogical organization in the hospitals, collaborating to discuss the gaps presented in the hospital educational system. However, the work performed by the Sareh program has shown big results, be of social or cognitive order, but, mainly, in the process of learning of the hospitalized student. We hope with this research to encourage new studies about the hospital reality, to support new concepts about the curriculum of the universities that graduate the teaching professionals. To the hospitalized students , it is essencial, because, besides permitting the students to keep studying , it becomes them closer to their cultural, social and educational reality.